The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1557/mrc.2019.51
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and adsorption performance research of large-volume hollow mesoporous polydopamine microcapsules

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…PDA, according to Nieto et al plays a primary role in and treatment of cancer, being per se an antineoplastic system, meaning it selectively kills cancer cells, especially in the case of breast cancer, without causing toxic effects to healthy cells [ 148 ]. A novel type of hollow PDA (HMPDA) was reported by Tao et al who demonstrated that morphology control of PDA and their surface properties are fundamental for nanomedicine applications [ 149 ]. Drug adsorption capability is in fact strictly correlated to PDA surface area and their strategy produced PDA with enhanced surface area, granting an improved drug loading.…”
Section: Mnp Based Therapy and Theranosticsmentioning
confidence: 99%
“…PDA, according to Nieto et al plays a primary role in and treatment of cancer, being per se an antineoplastic system, meaning it selectively kills cancer cells, especially in the case of breast cancer, without causing toxic effects to healthy cells [ 148 ]. A novel type of hollow PDA (HMPDA) was reported by Tao et al who demonstrated that morphology control of PDA and their surface properties are fundamental for nanomedicine applications [ 149 ]. Drug adsorption capability is in fact strictly correlated to PDA surface area and their strategy produced PDA with enhanced surface area, granting an improved drug loading.…”
Section: Mnp Based Therapy and Theranosticsmentioning
confidence: 99%
“…The PDA was coated onto CuMSN@DOX NPs by following the previous publications [48,55]. Initially, 50 mg of CuMSN@DOX NPs were added into 1 mg/mL solution of dopamine hydrochloride in Tris buffer (10 mM, pH 8.5) and continuously stirred under dark conditions at room temperature for 10 h. PDA-coated black-colored solid was collected by centrifugation and washed thrice with distilled water to remove un-polymerized dopamine molecules from the surface.…”
Section: Pda Coating Onto Cumsn@doxmentioning
confidence: 99%
“…Furthermore, in vitro synthesis of melanin offers the possibility to manipulate the size and surface characteristics of the particles. Consequently, both the loading efficiency and the release of the drug can be controlled, as the drug adsorption capability of synthetic melanin is dependent on its surface area [ 30 ]. Melanin, once injected, makes a local depot for several weeks, allowing local release.…”
Section: Potential Applications Of Melanin In Medicinementioning
confidence: 99%